CSC565: Software Engineering / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics And Media (Universiti Teknologi MARA (UiTM), 2023)
The subject introduces the theories and practices of Software Engineering which includes requirement analysis, design, coding, testing, validation, verification and maintenance. Students will collaboratively define requirements, design and implement a mini project using CASE tools. Upon successful completion of the module, students will have demonstrated knowledge of the strengths and weaknesses of the software development lifecycle and the ability to design and develop software solutions for a given problem. Apply and reflect upon project management techniques used to solve a given problem.